The American city : what works, what doesn't - Garvin, Alexander (New York : McGraw-Hill Education, 2013)
'Now in full color! The third edition of THE standard reference work on urban planning and design features new projects and the latest developments in the industry.In the Third Edition of The American City: What Works, What Doesn't, practicing city planner and noted urban scholar Alexander Garvin surveys what has been done to improve America's cities over the past 100 years--analyzing more than 300 programs and projects. This fully updated edition presents newly named and reorganized chapters, the latest statistical information on existing projects, new and updated illustrations, and new projects that have been completed in the decade since the previous edition was published.Taking a rare multidisciplinary approach, Garvin shows how the combination of individual and private-sector efforts, community-level action, and broad-based government policy can and has achieved urban regeneration. He explains that by studying and learning from the past, we can solve modern crises such as the scarcity of public open space, the lack of safe, affordable housing, the degradation of the environment, the erosion of the tax base, and countless other problems plague our cities and suburbs. The book presents six ingredients of project success--market, location, design, financing, entrepreneurship, and time.New to this Edition: Now in full color New sections--Downtown Strategies; Housing Strategies; Suburban Strategies; Regulatory Strategies--and section introductions New developments such as the subprime mortgage crisis New projects, including redevelopment of the World Trade Center site; Atlantic Station in Atlanta; Millennium Park in Chicago; Highline in NYC Reworked, renamed, and reorganized chapters Updated statistics 85 new illustrations and nearly 100 updated illustrations'--
'Now in full color! The third edition of THE standard reference work on urban planning and design features new projects and the latest developments in the industry'--
Keywords: City planning -- United States -- Case studies